PROJECT MANAGEMENT METHODOLOGY FOR GRANT ACTIVITIES FOR INCLUSIVE DEVELOPMENT: INNOVATIVE TECHNOLOGIES AND NATIONAL SECURITY CHALLENGES - SHESTAKOVSKA, Tetyana; YAROVOY, Tikhon; HAVRILECHKO, Yuriy (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the methodological principles of grant project management aimed at ensuring inclusive development through the implementation of innovative initiatives. Grant programs play an important role in stimulating economic growth, supporting educational, scientific, environmental and social projects that contribute to sustainable development and equal access to opportunities. At the same time, effective management of grant projects requires modern methodological approaches that take into account digital transformation, strategic planning tools and risks associated with national security. The article examines key technologies used in grant activities, in particular blockchain to increase transparency of financing and monitoring of costs, artificial intelligence and big data to assess the effectiveness of projects and predict their impact, cloud technologies for data management and digital identification to protect information and minimize cyber threats. Innovative approaches allow to optimize management processes, ensure efficient use of resources and increase the effectiveness of grant projects. Special attention is paid to challenges related to national security. The main threats identified include financial risks associated with fraud and misuse of grant funds, cybersecurity and possible attacks on the information systems of grantors and grantees, economic instability due to dependence on external funding, as well as social and political risks that may arise from insufficient integration of grant initiatives into public policy. Measures are proposed to improve the management of grant projects, in particular, the implementation of digital control and audit mechanisms, the integration of international transparency standards, strengthening public-private partnerships and expanding opportunities for the participation of Ukrainian organizations in international grant programs. The results of the study may be useful for state bodies, scientists, grantors and grant recipients, contributing to the development of an effective grant management system in Ukraine.